Novel Application of Localized Nanodelivery of Anti–Interleukin‐6 Protects Organ Transplant From Ischemia–Reperfusion Injuries. Issue 9 (18th April 2017) - Solhjou, Z.; Uehara, M.; Bahmani, B.; Maarouf, O. H.; Ichimura, T.; Brooks, C. R.; Xu, W.; Yilmaz, M.; Elkhal, A.; Tullius, S. G.; Guleria, I.; McGrath, M. M.; et al.
Abstract : Ischemia–reperfusion injury (IRI) evokes intragraft inflammatory responses, which markedly augment alloimmune responses against the graft. Understanding the mechanisms underlying these responses is fundamental to develop therapeutic regimens to prevent/ameliorate organ IRI. Here, we demonstrate that IRI results in a marked increase in mitochondrial damage and autophagy in dendritic cells (DCs). While autophagy is a survival mechanism for ischemic DCs, it also augments their production of interleukin (IL)‐6. Allograft‐derived dendritic cells (ADDCs) lacking autophagy‐related gene 5 (Atg5) showed higher death rates posttransplantation. Transplanted ischemic hearts from CD11cCre/Atg5 conditional knockout mice showed marked reduction in intragraft expression of IL‐6 compared with controls. To antagonize the effect of IL‐6 locally in the heart, we synthesized novel anti–IL‐6 nanoparticles with capacity for controlled release of anti–IL‐6 over time. Compared with systemic delivery of anti–IL‐6, localized delivery of anti–IL‐6 significantly reduced chronic rejection with a markedly lower amount administered. Despite improved allograft histology, there were no changes to splenic T cell populations, illustrating the importance of local IL‐6 in driving chronic rejection after IRI. These data carry potential clinical significance by identifying an innovative, targeted strategy to manipulate organs before transplantation to diminish inflammation, leading to improved long‐term outcomes. Abstract : Ischemia–reperfusion injury increases dendritic cell autophagy and production of interleukin‐6, enhancing chronic rejection.